Comparison of Community-Associated and Health Care-Associated Methicillin-Resistant Staphylococcus aureus in Canada: Results from CANWARD 2007 - Kimberly A Nichol; Melissa McCracken; Melanie R DeCorby; Kristjan Thompson; Michael R Mulvey; James A Karlowsky; Daryl J Hoban; George G Zhanel (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) differ from health care-associated MRSA (HA-MRSA) in their genotypic and phenotypic characteristics. The purpose of the present study was to compare the demographics, antimicrobial susceptibilities and molecular epidemiology of CA-MRSA and HA-MRSA in Canada. METHODS: In 2007, 385 MRSA isolates were collected from Canadian patients attending hospital clinics, emergency rooms, medical/ surgical wards and intensive care units. Susceptibilities to betalactams, clarithromycin, clindamycin, daptomycin, levofloxacin, linezolid, moxifloxacin, tigecycline, trimethoprim-sulfamethoxazole and vancomycin were determined by Clinical and Laboratory Standards Institute broth microdilution. Strain typing was performed by pulsed-field gel electrophoresis (PFGE) and the mecA, nuc and pvl genes were detected by polymerase chain reaction. RESULTS: Of the 385 MRSA, 19.5% were CA-MRSA and 79.2% were HA-MRSA as determined by PFGE. CA-MRSA belonged to PFGE types CMRSA10/USA300 (66.7%) and CMRSA7/USA400 (33.3%); PFGE types identified among HA-MRSA included CMRSA2/USA100/800 (81.6%), CMRSA6 (13.1%), CMRSA1/ USA600 (3.3%), CMRSA5/USA500 (1.3%), CMRSA3 (0.3%) and CMRSA9 (0.3%). Panton-Valentine leukocidin (PVL) was detected in 94.7% of CA-MRSA and 0.7% of HA-MRSA. Resistance rates (CA-MRSA versus HA-MRSA) were 61.3% versus 97.7% to levofloxacin, 73.3% versus 96.7% to clarithromycin, 12.0% versus 74.8% to clindamycin and 0.0% versus 15.4% to trimethoprim-sulfamethoxazole. No MRSA were resistant to vancomycin, linezolid, tigecycline or daptomycin. CONCLUSIONS: CA-MRSA represented 19.5% of all MRSA. CA-MRSA was significantly more susceptible to levofloxacin, clarithromycin, clindamycin and trimethoprim-sulfamethoxazole than HA-MRSA. Of CA-MRSA, 94.7% were PVL-positive while 99.3% of HA-MRSA were PVL-negative. CA-MRSA is an emerging pathogen in Canadian hospitals.